Meaning of Public Interests and Business-Economic Legal Interests in Development (Case Study of the Development of PT Semen Indonesia in Rembang) - Salsabila, Aldhanalia Pramesti; Riandini, Vera Ayu (Lex Scientia Law Review, 2019)
The meaning of community interests and business-economic interests for development is very important in the Indonesian context, both from a juridical and social setting. First, land and environmental procurement activities for development are activities that will continue as long as the Indonesian state carries out development. Two interests will continue to face each other, namely the interests of the state who need land on the one hand and the interests of individuals or groups of people who own or control land rights, in the other sense, the people who will be affected. PT Semen Indonesia's construction plan has raised objections from most residents of Rembang. Many environmental activists also criticized the project. They consider the construction of PT Semen Indonesia to be a mining crime, as revealed by the coordinator for economic, social and cultural rights advocacy (ekosob). On the other hand, the Government, both the Central Government, the Provincial Government and the Rembang Regency Government, remains committed to continuing this project as an economic resource that will benefit the wider community. It is hoped that the success of this project will open up large employment opportunities and will benefit many people. One of the main obstacles is related to land acquisition or land acquisition issues and environmental and even business-economic problems if the project is canceled due to the influx of investors of approximately 4.7 trillion rupiah for the construction of this project.